LEARNING STYLE OF USIM UDERGRADUATE DENTAL STUDENTS - Aws H Ali AL-Kadhim; Syafiq Alauddin; Norazlina Mohammad; Azlan Jafaar; Sarah Taha AL-Ani (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Background and Objectives: Every dental student has his/her own learning style. As dental educators, it is mandatory to identify the fact that each individual student may have an inclination of obtaining knowledge and skill in one style over another. The aim of the present study was to determine the learning style preferences of dental students using the Visual, Aural, Read, Write, Kinesthetic (VARK) questionnaire. Materials and Methods: The VARK questionnaire was distributed to determine the student’s preferred mode of learning. Completed questionnaires were scored and tabulated to determine the distribution of VARK preferences. Results: A total of 156 (89%) questionnaires were returned for further analysis. Majority of students have preferred a quad modal style of learning. Whilst only 6.5% from year 1, 5.7% from year 4 and 10% from year 5 who preferred a trimodal. Conclusion: The dental students in this study had varied learning preferences. As dental educators, we need to adopt different methods of teaching in order to reach most of the students and make the educational experience more productive.